Party Summer - Stine, R. L. (London An Archway Paperback, 1991)
"Cari Taylor and her three friends look forward to a "party summer", working at The Howling Wolf Inn, an old hotel on a tiny island off Cape Cod. But to their dismay, the hotel is completely deserted, and someone warns them to leave immediately. The mysterious owner, Simon Fear III, allows Cari and her friends to stay, giving them the run of the hotel. The four teenagers are thrilled ... until they realize they have been put up in the "haunted wing"... until Simon's weird and frightening brother appears ... until they hear a woman screaming, "No party-please, no party!"... until the walls and the faucets begin to drip blood! When Simon Fear is murdered, Cari and her horrified friends want out. But they can't escape! They're trapped on the island. And that's when the "party" begins."-
Keywords: Haunted hotels -- Massachusetts--Cape Cod -- Teenagers